Aphidophagous Parasitoids can Forage Wheat Crops Before Aphid Infestation, Parana State, Brazil. Issue 1 (5th April 2015) - Ceolin Bortolotto, Orcial; de Oliveira Menezes Júnior, Ayres; Thibes Hoshino, Adriano
Abstract : Aphid parasitoids are common in Brazilian wheat fields, and parasitize aphids at the wheat tillering stage. However, there is little information available about when this natural enemy occurs in wheat crops. This study investigated the initial occurrence of aphid parasitoids in four commercial wheat crops in northern Paraná during the 2009 crop season. We installed two Malaise traps at each wheat farm, and 400 tillers were assessed weekly in each field for aphid abundance. During this study, we captured 4, 355 aphid parasitoids and 197 aphids. Three species of braconid parasitoids were identified, including Aphidius colemani (Viereck 1912), Lysiphlebus testaceipes (Cresson 1880), and Diaeretiella rapae (McIntosh 1855). The aphids species identified were Rhopalosiphum padi (Linnaeus 1758) and Sitobion avenae (Fabricius 1775). This study showed that aphid parasitoids are present in wheat crops even when aphid densities are low, and in one farm, occurred before the aphids colonization. These reports can justified the high efficiency of these natural enemies against aphids in wheat fields.